PENGARUH PENGGUNAAN MULTIMEDIA PEMBELAJARAN INTERAKTIF PENGINDERAAN JAUH TERHADAP HASIL BELAJAR GEOGRAFI - Fitria Hanim; Sumarmi Sumarmi; Ach. Amirudin (Graduate School of Universitas Negeri Malang, 2016)
This research aims to determine the extent of multimedia interactive learning remote sensing effect on student learning outcomes in MAN I Malang. Using a quasi experimental study using a non equivalent control group design, this design only in the experimental group and the control group was not chosen at random. The samples were all students of class XII IPS MAN I Malang. The research instrument used was a test. The analysis technique used is the t-test and Cohen'sd Online Calculator for the effectiveness of the use of multimedia in teaching. The results showed that the use of interactive learning multimedia remote sensing effect on learning outcomes, where the results obtained in the experimental class, the mean standard deviation of 74.24 with 7.267 greater than the control class that has a mean 60.21 with a standard deviation of 9.955. Results gain score showed the difference between pretest and posttest values obtained in experimental classes with an average yield gain score of = 0.7 are included in the high category. While the calculations produced 1,610 Cohen'sd online calculator which is regarded as a relatively large effect size, then Ho is rejected and Ha accepted. It means that there is a significant influence on the use of remote sensing multimedia interactive learning on learning outcomes in MAN I Malang.Penelitian ini bertujuan untuk mengetahui sejauh mana multimedia pembelajaran interaktif penginderaan jauh berpengaruh terhadap hasil belajar siswa di MAN I Malang. Penelitian menggunakan eksperimen quasi dengan menggunakan non equivalent control group design, hanya pada desain ini kelompok eksperimen dan kelompok kontrol tidak dipilih secara random. Sampel penelitian adalah seluruh siswa kelas XII IPS MAN I Malang. Instrumen penelitian yang digunakan adalah tes. Teknik analisis yang digunakan adalah uji-t. Hasil penelitian menunjukkan bahwa penggunaan multimedia pembelajaran interaktif penginderaan jauh berpengaruh terhadap hasil belajar, dimana hasil yang diperoleh pada kelas eksperimen, diperoleh mean 74,24 dengan standar deviasi 7,267 lebih besar daripada kelas kontrol yang memiliki mean 60,21 dengan standar deviasi 9,955. Hasil gain score menunjukkan selisih antara nilai pretes dan postes didapatkan pada kelas ekperimen dengan hasil rata-rata gain score, yaitu = 0,7 yang masuk dalam kategori tinggi, maka Ho ditolak dan Ha diterima. Artinya, ada pengaruh yang signifikan pada penggunaan multimedia pembelajaran interaktif penginderaan jauh terhadap hasil belajar di MAN I Malang.